Mitochondrial Calcium Uniporter MCU Supports Cytoplasmic Ca2+ Oscillations, Store-Operated Ca2+ Entry and Ca2+-Dependent Gene Expression in Response to Receptor Stimulation - Samanta, Krishna (Public Library of Science, 2014)
Ca2+ flux into mitochondria is an important regulator of cytoplasmic Ca2+ signals, energy production and cell death pathways. Ca2+ uptake can occur through the recently discovered mitochondrial uniporter channel (MCU) but whether the MCU is involved in shaping Ca2+ signals and downstream responses to physiological levels of receptor stimulation is unknown. Here, we show that modest stimulation of leukotriene receptors with the pro-inflammatory signal LTC4 evokes a series of cytoplasmic Ca2+ oscillations that are rapidly and faithfully propagated into mitochondrial matrix. Knockdown of MCU or mitochondrial depolarisation, to reduce the driving force for Ca2+ entry into the matrix, prevents the mitochondrial Ca2+ rise and accelerates run down of the oscillations. The loss of cytoplasmic Ca2+ oscillations appeared to be a consequence of enhanced Ca2+-dependent inactivation of InsP3 receptors, which arose from the loss of mitochondrial Ca2+ buffering. Ca2+ dependent gene expression in response to leukotriene receptor activation was suppressed following knockdown of the MCU. In addition to buffering Ca2+ release, mitochondria also sequestrated Ca2+ entry through store-operated Ca2+ channels and this too was prevented following loss of MCU. MCU is therefore an important regulator of physiological pulses of cytoplasmic Ca2+.